ELT Teacher's Opinion on The Utilization of Social Media In English Classroom - Joko Prayudha (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Education at this time is inseparable from technological advances; even technology is the result of knowledge that is passed on through the educational process. The use of social media to communicate or simply entertain is one of the technologies that we use the most in our daily lives. Therefore, this study tries to investigate students' opinion on the utilization of social media in English classroom. This study uses qualitative methods through a descriptive approach. Data was collected in two ways: first, by collecting literature related to the use of social media in learning English, and second, by interviewing three English teachers regarding their opinions on the use of social media in teaching English. Data were analyzed through three stages proposed by Miles and Huberman (2013), namely data reduction, data display, and conclusion. The results of the study show that the use of social media in teaching English has a positive impact on learning English, where students would become more confident, creative, innovative, independent, flexible, fun, and it can improve the learning atmosphere, more interactive, and be able to learn from a wide variety of sources so as to encourage them to improve their English skills.